Demonstration of differences in colonic volumes, transit, chyme consistency, and response to psyllium between healthy and constipated subjects using magnetic resonance imaging. Issue 9 (30th July 2018) - Major, G.; Murray, K.; Singh, G.; Nowak, A.; Hoad, C. L.; Marciani, L.; Silos‐Santiago, A.; Kurtz, C. B.; Johnston, J. M.; Gowland, P.; Spiller, R.
Abstract: Background: In functional gastrointestinal disorders a lack of objective biomarkers limits evaluation of underlying mechanisms. We aimed to demonstrate the utility of magnetic resonance imaging for this task using psyllium, an effective constipation treatment, in patients and controls. Methods: Two crossover studies: (i) adults without constipation (controls, n = 9) took three treatments in randomized order for 6 days – maltodextrin (placebo), psyllium 3.5 g t.d.s and 7 g t.d.s., (ii) adults with chronic constipation (patients, n = 20) took placebo and psyllium 7 g t.d.s. for 6 days. MRI was performed fasting and postprandially on day 6. Measurements included small bowel and ascending colon water content, colonic volume, transit time, and MR relaxometry (T1, T2) to assess colonic chyme. Stool water percentage was measured. Results: 7 g psyllium t.d.s. increased fasting colonic volumes in controls from median 372 mL (IQR 284‐601) to 578 mL (IQR 510‐882), and in patients from median 831 mL (IQR 745‐934) to 1104 mL (847‐1316), P < .05. Mean postprandial small bowel water was higher in controls and patients after 7 g psyllium t.d.s. vs placebo. Whole gut transit was slower in patients than controls ( P < .05). T1 of the descending colon chyme (fasting) was lower in patients (213 ms, 176‐420) than controls (440 ms, 352‐884, P < .05) on placebo, but increased by 7 g psyllium t.d.s. (590 ms, 446‐1338), P < .001. Descending colon T1 correlated with baseline stool water content and stool frequency on treatment. Conclusions and Inferences: MRI measurements can objectively demonstrate the mode of action of therapy targeting intestinal fluid content in constipation. Abstract : We aimed to test the utility of magnetic resonance imaging to provide multiparametric assessment of gastrointestinal factors contributing to constipation, and their response to psyllium therapy. Colonic volume and whole gut transit times were greater in constipation than in health. Psyllium increased colonic volume but also intestinal water content as predicted, illustrating the potential for MRI to provide mechanistic evaluation of constipation and treatment.